2017
DOI: 10.1111/bph.13831
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inflammation and nitric oxide upon platelet aggregation following deposition of diesel exhaust particles in the airways

Abstract: Background and PurposeExposure to nanoparticulate pollution has been implicated in platelet‐driven thrombotic events such as myocardial infarction. Inflammation and impairment of NO bioavailability have been proposed as potential causative mechanisms. It is unclear, however, whether airways exposure to combustion‐derived nanoparticles such as diesel exhaust particles (DEP) or carbon black (CB) can augment platelet aggregation in vivo and the underlying mechanisms remain undefined. We aimed to investigate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
(76 reference statements)
0
15
0
2
Order By: Relevance
“…PRG1-1 treatment increased the expression levels of iNOS and COX-2, both of which are associated with NO production. The release of NO is involved in many physiological processes, such as vasodilatation (Khan et al, 2017), neurotransmission (Kusek et al, 2017), immune responses (Cinzia, Maria Pia, Angela, & Marco, 2016), and platelet aggregation (Smyth et al, 2017). Furthermore, activated macrophages produce cytokines, including IL-6 and TNF-α, that play important roles in the cellular immune process by aiding in the elimination of abnormal cells (Ying et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…PRG1-1 treatment increased the expression levels of iNOS and COX-2, both of which are associated with NO production. The release of NO is involved in many physiological processes, such as vasodilatation (Khan et al, 2017), neurotransmission (Kusek et al, 2017), immune responses (Cinzia, Maria Pia, Angela, & Marco, 2016), and platelet aggregation (Smyth et al, 2017). Furthermore, activated macrophages produce cytokines, including IL-6 and TNF-α, that play important roles in the cellular immune process by aiding in the elimination of abnormal cells (Ying et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The link between inflammation and thrombosis at later time points after pulmonary instillation is possible (6–24 h), but complex [ 69 ]. Smyth et al (2017) showed intratracheally instillation of DEP (25 μg) in mice to induce platelet aggregation independent of lung inflammation [ 70 ]. The study also showed that platelet aggregation persisted in endothelial nitric oxide synthase (eNOS) knockout mice [ 70 ], suggesting a lesser influence of vascular-derived mediators in actions of DEP on platelets.…”
Section: In Vivo Studies In Animalsmentioning
confidence: 99%
“…
We read with great interest the recent study by Smyth et al, which claimed that diesel exhaust particles (DEP) instilled through the airway induce adverse effects such as inflammation, oxidative damage, and coagulopathy (Smyth et al, 2017). In their study, with regard to the impairments in coagulation, the authors only referred to the promoting effects of DEP on platelet aggregation.
…”
mentioning
confidence: 99%